Non-invasive assessment of porcine oocyte quality by supravital staining of cumulus–oocyte complexes with lissamine green B. Issue 3 (21st July 2015) - Dutta, Rahul; Li, Shun; Fischer, Konrad; Kind, Alexander; Flisikowska, Tatiana; Flisikowski, Krzysztof; Rottmann, Oswald; Schnieke, Angelika
Summary: We evaluated the usefulness of lissamine green B (LB) staining of cumulus–oocyte complexes (COC) as a non-invasive method of predicting maturational and developmental competence of slaughterhouse-derived porcine oocytes cultured in vitro. Cumulus cells of freshly aspirated COCs were evaluated either morphologically on the basis of thickness of cumulus cell layers, or stained with LB, which penetrates only non-viable cells. The extent of cumulus cell staining was taken as an inverse indicator of membrane integrity. The two methods of COC grading were then examined as predictors of nuclear maturation and development after parthenogenetic activation. In both cases LB staining proved a more reliable indicator than morphological assessment ( P < 0.05). The relationship between LB staining and cumulus cell apoptosis was also examined. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay for DNA fragmentation revealed that oocytes within COCs graded as low quality by either LB staining or visual morphology showed significantly greater DNA fragmentation ( P < 0.05) than higher grades, and that LB and visual grading were of similar predictive value. Expression of the stress response gene TP53 showed significantly higher expression in COCs graded as low quality by LB staining. However expression of the apoptosis-associated genes BAK and CASP3 was not significantly different between high or low grade COCs, suggesting that mRNA expression of BAK and CASP3 is not a reliable method of detecting apoptosis in porcine COCs. Evaluation of cumulus cell membrane integrity by lissamine green B staining thus provides a useful new tool to gain information about the maturational and developmental competence of porcine oocytes.